Perencanaan Persediaan Bahan Baku pada UMK Tiga Bersaudara Kota Kupang dengan Metode Economic Order Quantity (EOQ) - Seprianto E. Haobenu; Antonio E. L. Nyoko; Aldarine Molidya; Rolland E. Fanggidae (Penerbit Goodwood, 2021)
AbstractPurpose: This research is a form of raw material inventory planning using the Economic Order Quantity (EOQ) method for fried corn products at UMK Tiga Bersaudara Kupang City. Research Methodology: This research method used a quantitative approach. The data analysis technique used is forecasting, EOQ, and Safety Stock.Results: The outcome of this study is the creation of a raw material inventory that can be applied by the UMK Tiga Bersaudara in carrying out its production. The number of orders for raw materials has also been identified using the EOQ method. To avoid shortages of raw materials, a calculation of how much safety stock is needed in the next period has also been calculated. Limitation: This calculation is predictive so that the reality in the field can change in the future.Contribution: Companies are advised to plan raw material inventory using the methods used in this study, namely forecasting, EOQ, SS, and calculating the total cost of inventory.